Non-Hodgkin's lymphoma masquerading as splenic abscess: A case report. (September 2022) - Khan, Qaisar Ali; Mumtaz, Arif; Baqi, Abdul; Ain, Hoor Ul; Mahfooz, Rabia Salman; Asim, Nowshad; Iram, Sumaira; Hussien Mohamed Ahmed, Khabab Abbasher; Tahir, Muhammad Junaid; Yousaf, Zohaib
Abstract: Background: Non-Hodgkin's lymphoma (NHL) is a monoclonal proliferation of lymphoid cells from B lineage. Although NHLs are primarily hematological tumors of lymph nodes but rarely can involve extranodal sites such as the spleen. Case report: A 29-year-old female patient presented with low-grade fever, cough, anemia, weight loss, tender left hypochondrium, and splenomegaly. A hypodense lesion in the spleen with central necrosis, having strong positivity for common leukocyte antigen (LCA), CD 20, and CD 10, led to a diffuse large B cell lymphoma diagnosis. The patient had an excellent clinical post-splenectomy response to combination chemotherapy and immunotherapy. Conclusion: NHL can present with symptomatic extra-nodal involvement without enlarged lymph nodes. Highlights: Non-Hodgkin's lymphoma (NHL) is a group of malignant lymphoproliferative disorders (LPD) that primarily involve the lymph nodes. NHL is characterized by an irregular proliferation of T or B lymphocytes. Most NHLs are of B-cell origin. NHLs range from indolent malignancies (low-grade histology) to rapidly growing, highly aggressive tumors (high-grade histology). Extra-nodal involvement is common in the spleen, with prevalence being 20%–30%. Here we described a 29-year-old female patient presented with low-grade fever, cough, anemia, weight loss, tender left hypochondrium, and splenomegaly.